Implications of pacemaker implantation after TAVR: insights from the Nationwide Readmissions Database. (25th November 2020) - Sharma, E; Sheikh, W; Parulkar, A; Lima, F; Wu, M; Chu, A
Abstract: Introduction: Conduction disturbances after transcatheter aortic valve replacement (TAVR) requiring permanent pacemaker (PPM) implantation are a well-known procedural complication. Data on the effect of post-TAVR PPM implantation on 30-day readmissions is scarce. Methods: The Nationwide Readmissions Database (NRD) is a nationally representative sample of all US hospitalizations, representing over 35 million discharges. The 2016 NRD was used to identify patients who underwent TAVR and PPM implantation from January to November 2016. Propensity matching was used to balance baseline clinical characteristics. Results: Of the 44, 607 patients who underwent TAVR, 4, 878 (10.9%) required permanent pacemaker implantation during their index hospitalization. Patients requiring PPM during their index admission for TAVR had a higher crude median length of stay (LOS) (5d vs. 3d, p<0.001), median cost of index admission (61, 604 vs. 45, 513, p<0.001) and rate of 30-day readmission (14.5% vs 11.2%, p<0.001). After 2:1 propensity matching, PPM patients still had a higher median LOS (5d vs. 3d, p<0.001), median cost of index admission (61, 902 vs. 41, 162, p<0.001), and rate of 30-day readmission (13.8% vs 11.1%, p=0.003). Patients who received PPM were more likely to be older (81.1 vs 80.3, OR 1.01, CI 1.01–1.02), diabetic (OR 1.27, 1.13–1.44), obese (OR 1.22, 1.05–1.43), and have right (OR 4.35, 3.72–5.09) or left (OR 1.80, 1.51–2.15) bundle branch blocks on multivariate analysis. Causes of readmission in patients with and without PPM were predominantly non-cardiac (62.9% vs 68.0%). Heart failure was the most common cause of readmission for both groups (18.4% vs 14.6%). Median cost of readmissions (8716 vs 8250, p=0.34) and LOS (4d vs 4d, p=1) were not significantly different during readmissions. Conclusions: Based on a nationally representative sample, 10.9% of patients undergoing TAVR required PPM implantation during the index hospitalization. Age, diabetes, obesity, and right or left bundle branch blocks were significant predictors of PPM implantation. PPM implantation resulted in significantly higher LOS, costs, and 30-day readmissions on propensity-matched analysis. Funding Acknowledgement: Type of funding source: None